Immunoexpression of PD-L1 and PD-1 and Its Clinicopathological Correlation in Urothelial Carcinomas - Kumar, Utpal; Anthony, Michael Leonard; Sahai, Rishabh; Mittal, Ankur; Durgapal, Prashant; Kishore, Sanjeev (Journal of Laboratory Physicians, 2021)
Introduction Urothelial carcinomas are the most common types of bladder tumors that have recently shown a changing trend in treatment protocols with the introduction and approval of immune checkpoint inhibitors. The most important immune checkpoint lies with the PD-1–PD-L1 axis. Although multiple drugs have been approved, there is uncertainty about patient selection criteria and diagnostic assays. Recent studies related to the laboratory-developed tests have opened up the horizon of PD-1 and PD-L1 immunohistochemistry even at resource-constrained laboratories. We propose to study these immunohistochemistry markers in our laboratory using newer clones.Materials and Methods We selected 116 consecutive cases of transurethral bladder tumor resection from our laboratory archive and applied PD-1 and PD-L1 immunohistochemistry. The study was approved by the institution's ethics committee.Results We found high expression of PD-1 and PD-L1 in urothelial carcinoma even with different cut-offs of PD-L1. Muscle invasion, lamina invasion, and grade of carcinoma had a statistically significant effect on the expression; however, age and sex did not affect the expression.Conclusion Based on our current study, we can conclude that the clones used in our study show high expression in urothelial carcinoma and can aid in patient selection and treatment protocol, irrespective of age and sex.
Keywords: immune checkpoint inhibitors; PD-1; PD-L1; urothelial carcinoma